Criminal law: from liberal ideas to electoral manipulation - Saavedra-García, Joao Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Criminal law, due to the severity of its prescriptions, must arise from thoughtful and inclusive analysis, and based on a serious and responsible discussion of its convenience, to promote the adoption of wise provisions. Unfortunately, this situation is completely contrary to what happens in reality, as punitive measures are taken by action committees and political advisers, driven by thirst for revenge, the electoral interests and the use of the constant state of anxiety of citizens. For these reasons, are repeatedly promulgated populist and politicized criminal laws that aim at repression and concealment of social problems; circumstance that places the interests of the few over the majority and that, in turn, sacrifices instrumental function of criminal law to give it a merely symbolic function.